Reduction of hyaluronan and increased expression of HYBID (alias CEMIP and KIAA1199) correlate with clinical symptoms in photoaged skin. (1st July 2018) - Yoshida, H.; Nagaoka, A.; Komiya, A.; Aoki, M.; Nakamura, S.; Morikawa, T.; Ohtsuki, R.; Sayo, T.; Okada, Y.; Takahashi, Y.
Summary: Background: Hyaluronan (HA) metabolism in skin fibroblasts is mediated by HYBID (hyaluronan binding protein involved in hyaluronan depolymerization, alias CEMIP and KIAA1199) and the HA synthases HAS1 and HAS2. However, photoageing‐dependent changes in HA and their molecular mechanisms, and the relationship between HA metabolism and clinical symptoms in photoaged skin remain elusive. Objectives: We examined the amount, size and tissue distribution of HA and expression levels of HYBID, HAS1 and HAS2 in photoaged skin, and analysed their relationship with the degree of photoageing. Methods: Photoageing‐dependent changes of HA were investigated by studying skin biopsies isolated from photoprotected and photoexposed areas of the same donors, and the relationships between HA and photoageing symptoms such as skin wrinkling and sagging were examined. Results: Skin biopsy specimens showed that the amount and size of HA are decreased in photoexposed skin compared with photoprotected skin, and this was accompanied by increased expression of HYBID and decreased expression of HAS1 and HAS2 . Histologically, HA staining in the papillary dermis was decreased in photoexposed skin, showing reverse correlation with HYBID expression. HYBID expression in the photoexposed skin directly correlated with skin roughness and sagging parameters, and the reduced HA staining in the papillary dermis in the photoexposed skin positively correlated with these symptoms. Conclusions: These data demonstrate that imbalance between HYBID‐mediated HA degradation and HAS‐mediated HA synthesis may contribute to enhanced HA catabolism in photoaged skin, and suggest that HYBID‐mediated HA reduction in the papillary dermis is related to skin wrinkling and sagging of photoaged skin.